OC-070 Endoscopic mucosal resection in the elderly. (17th June 2017) - Gaglia, A; Skouras, T; Bond, A; Lim, MJ; Bonnet, L; Sarkar, S
Abstract : Introduction: Endoscopic mucosal resection (EMR) is an invaluable and effective technique of resecting colorectal (CR) polyps. However, the outcomes and usefulness in elderly patients is unknown. The aim of the study was to determine the outcomes of elderly persons undergoing EMR of CR polyps and to quantify the survival and predictors of mortality Method: Retrospective cohort study of persons aged ≥75 years old who underwent EMR over 10 years (2005–2014) at a tertiary university centre. Age, gender, Charlson score (comorbidity index), repeat colonoscopies and polyp characteristics were investigated to identify potential predictors of post EMR survival. Results: 208 patients (mean age 80.9±3.67 years; 114 male, 94 female) with median Charlson score 1 (IQR 0–2) were included. The median size of the polyps was 20 mm (range 10–150 mm). There were 50 deaths (24%) during the follow up period. All patients but one, who died from colorectal cancer, died from their comorbidities. The mean overall survival was 6.7±0.3 years (median 7.25 years). The complication rate was low at 2.5% and included 2 cases (0.9%)of post EMR bleeding with no need for re-intervention and no perforations. The 7 day readmission rate was 5.3% and the 30 day mortality post procedure was 0%. Predictors of Survival: Table 1 shows only the statistical significant factors of the univariate and multivariate analysis. Age≥80, Charson score ≥3 and histology of high grade dysplasia were predictors of significantly shorter survival. Repeat procedures had a survival benefit. Patients with a Charlson Index of <3 had approximately 20 month survival benefit (see table 2). Charlson score and age were independent predictor factors of mortality and no interaction was found between them in the multivariate analysis(p=0.83). Conclusion: EMR appeared to be a safe procedure in this cohort of elders. Age≥80 and Charlson score ≥3 were independent predictors of death. The latter is not normally recorded in routine assessment for endoscopy and may be important to the individualised decision making when considering an EMR in the Elderly. Disclosure of Interest: None Declared